The revolutionary (Translation of Kazi Nazrul Islam's Kuhelika) - Quayum, Mohammad Abdul (Nymphea Press, 2016)
This is a translation of Bangladesh National Poet Kazi Nazrul Islam's third and final novel, Kuhelika (1930). The story is about a Muslim youth who rebels against the British imperial rule and joins hands with a group of Hindu youths to fight off the colonial rule and attain India's political freedom. However, eventually he is caught by the colonial police and sent into exile.